New crystal packing arrangements in radical cation salts of BEDT-TTF with [Cr(NCS)6]3− and [Cr(NCS)5(NH3)]2−. (14th December 2015) - Brooks, Andrew C.; Martin, Lee; Day, Peter; Clegg, William; Harrington, Ross W.; Wallis, John D.
Graphical abstract: Crystal structures of a series of radical cation salts of BEDT-TTF with [Cr(NCS)6 ] 3− and [Cr(NCS)5 (NH3 )] 2− illustrate how the closely packed layers of donor molecules accommodate the insertion of thiocyanate ligands from the anion by either formation of "tube" motifs or inclusion of an aromatic solvent in the donor layer. Abstract: BEDT-TTF forms three packing arrangement styles in its radical cation salts with [Cr(NCS)6 ] 3 − in two of which two trans -oriented isothiocyanate ligands penetrate the BEDT-TTF layers either at the point where a solvent (nitrobenzene) is incorporated in a stack of donors or by four donor molecules forming a "tube" motif to accept a ligand at each end along with a small solvent molecule in between (acetonitrile). The [Cr(NCS)5 NH3 ] 2 − ion forms a related crystal packing arrangement with BEDT-TTF with a reduction in the number of "tube" motifs needed to accept an isothiocyanate ligand.